2015
DOI: 10.1021/acs.inorgchem.5b00308
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Organo-Rare-Earth Metal Monoalkyl Complexes Supported by Carbon σ-Bonded Indolyl Ligands: High Specific Isoprene 1,4-Cis Polymerization Catalysts

Abstract: A series of N-protected 3-imino-functionalized indolyl ligands 1-R-3-(R'N═CH)C8H5N [R = Bn, R' = 2,6-(i)Pr2C6H3 (HL(1)); R = CH3, R' = 2,6-(i)Pr2C6H3 (HL(2)); R = Bn, R' = (t)Bu (HL(3))] and 1-CH3-2-(2,6-(i)Pr2C6H3N═CH)C8H5N (HL(4)) was prepared via reactions of N-protected indolyl aldehydes with corresponding amines. The C-H σ-bond metathesis followed by alkane elimination reactions between RE(CH2SiMe3)3(thf)2 and HL(1)-HL(3) afforded the carbon σ-bonded indolyl-ligated rare-earth metal monoalkyl complexes. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 55 publications
1
21
0
Order By: Relevance
“…From Table 1, it is found that the Ho−C1 bond lengths, 2.551(5) and 2.652(5) Å, and the Er−C1 bond lengths, 2.538 (3) and 2.621(3) Å, are close to those of the Y−C1 bond lengths of 2.551(8) and 2.665(8) Å and the Yb−C1 bond lengths of 2.506(12) and 2.654(10) Å, 19 which is consistent with their ionic radii (Ho 3+ ≈ Y 3+ > Er 3+ > Yb 3+ ). However, Er−C1 bond lengths of complex 1b are significantly longer than the bond lengths of Er1−C(sp 2 ), 2.457(3) and 2.466(4) Å, of carbon σbonded indolyl supported rare-earth-metal alkyl complex L 2 ErCH 2 SiMe 3 (L = 1-Me-3-(2,6-iPr 2 C 6 H 3 NCH)C 8 H 5 N), 18 which might be due to the bridging μ 2 -η 1 :η 1 mode.…”
Section: ■ Results and Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…From Table 1, it is found that the Ho−C1 bond lengths, 2.551(5) and 2.652(5) Å, and the Er−C1 bond lengths, 2.538 (3) and 2.621(3) Å, are close to those of the Y−C1 bond lengths of 2.551(8) and 2.665(8) Å and the Yb−C1 bond lengths of 2.506(12) and 2.654(10) Å, 19 which is consistent with their ionic radii (Ho 3+ ≈ Y 3+ > Er 3+ > Yb 3+ ). However, Er−C1 bond lengths of complex 1b are significantly longer than the bond lengths of Er1−C(sp 2 ), 2.457(3) and 2.466(4) Å, of carbon σbonded indolyl supported rare-earth-metal alkyl complex L 2 ErCH 2 SiMe 3 (L = 1-Me-3-(2,6-iPr 2 C 6 H 3 NCH)C 8 H 5 N), 18 which might be due to the bridging μ 2 -η 1 :η 1 mode.…”
Section: ■ Results and Discussionmentioning
confidence: 92%
“…19 This result is different from our recent findings that the reactions of rare-earth-metal alkyls Yb(CH 2 SiMe 3 ) 3 (THF) 2 with 3-(tertbutylimino)indole 3-(tBuNCH)C 8 H 4 NH (L 1 ) produced dinuclear ytterbium complexes having indolyl ligands in μη 2 :η 1 :η 1 hapacities through alkyl insertion, while no C−H bond activation has been observed in the process. 17a We have also found that the reactions of 1-alkyl-3-imino-functionalized indoles with RE(CH 2 SiMe 3 ) 3 (THF) 2 provided the carbon σbonded indolyl-supported rare-earth-metal alkyl complexes through sp 2 C−H activation, 18 which is believed to be produced via an imino-coordination-promoted process. It has also been proposed that the activation of the α-C−H bond of pyridine 8,9 or imidazole 20 The anilido group of D then abstracted a proton from the released amine HN(SiMe 3 ) 2 to give the aniline-coordinated hexanuclear rare-earth-metal complexes 5 and lithium amide LiN(SiMe 3 ) 2 .…”
Section: ■ Results and Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…15 It is also different from the results of reactions of 1-alkyl-3-iminofunctionalized indoles with RE(CH 2 SiMe 3 ) 3 (THF) 2 producing only the 2-indolyl complexes. 16 All complexes were characterized by spectroscopic methods and elemental analyses, and their structures were further confirmed by single-crystal X-ray crystallographic analyses. The diamagnetic complex 1a was characterized by nuclear magnetic resonance (NMR) spectroscopy.…”
Section: ■ Introductionmentioning
confidence: 99%